Bimetallic Ni–Ru and Ni–Re Catalysts for Dry Reforming of Methane: Understanding the Synergies of the Selected Promoters - Álvarez Moreno, Andrea; Ramirez-Reina, Tomás; Ivanova, Svetlana; Roger, Anne-Cécile; Centeno, Miguel Ángel; Odriozola, José Antonio (Frontiers in Chemistry, 2021)
Designing an economical viable catalyst that maintains high catalytic activity and stability, is the key to unlock the dry reforming of methane (DRM) as a primary strategy for biogas valorization. Ni/Al2O3 catalysts have been widely used for this purpose; however, several modifications have been reported in the last years in order to prevent coke deposition and deactivation of the samples. Modification of the acidity of the support, and the addition of noble metal promoters, are between the most reported strategies. Nevertheless, in the task of designing an active and stable catalyst for DRM, the selection of an appropriate noble metal promoter is turning more challenging owed to the lack of homogeneity of the different studies. Therefore, this paper, aims to compare Ru (0.50 and 2.0%) and Re (0.50 and 2.0%) as noble metal promoters for a Ni/MgAl2O4 catalyst under the same synthesis and reaction conditions. Catalysts were characterized by XRF, BET, XRD, TPR, hydrogen chemisorption (H2-TPD) and dry reforming reaction tests. Results show that both promoters increase Ni reducibility and dispersion. However, Ru seems a better promoter for DRM since 0.50% of Ru increases the catalytic activity in 10% and leads to less coke deposition